PACS2001. Proceedings of the 2001 Particle Accelerator Conference (Cat. No.01CH37268)
DOI: 10.1109/pac.2001.987580
|View full text |Cite
|
Sign up to set email alerts
|

Extreme high vacuum technology for particle accelerators

Abstract: Linearly distributed pumping is highly desirable for Storage Rings to limit the pressure rise due to the outgassing induced by the circulating beams. As a byproduct, linear pumping allows extremely low pressures (down to the 10 -14 Torr range) to be achieved in static vacuum conditions. Non Evaporable Getters (NEGs), in the form either of a strip as adopted for LEP or of a thin film coating, may provide linear pumping in a simple and economic way. Compared to the strip, thin film coatings present the additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The authors reported that the modified Helmer gauge was able to measure pressure in the 10-12 Pa range (with an electron current of 3 mA an ion current of 10-15 A could be detected). The C. Benvenuti conclusion was "IHG (Improved Helmer Gauge) provides accurate measurements in the 10-14 torr range, but it perturbs the pressure to be measured" probably measuring its own outgassing [72]. This kind of gauge is still used at CERN for XHV measurements.…”
Section: Hot Cathode Ion Gaugesmentioning
confidence: 99%
“…The authors reported that the modified Helmer gauge was able to measure pressure in the 10-12 Pa range (with an electron current of 3 mA an ion current of 10-15 A could be detected). The C. Benvenuti conclusion was "IHG (Improved Helmer Gauge) provides accurate measurements in the 10-14 torr range, but it perturbs the pressure to be measured" probably measuring its own outgassing [72]. This kind of gauge is still used at CERN for XHV measurements.…”
Section: Hot Cathode Ion Gaugesmentioning
confidence: 99%